2021
DOI: 10.1186/s41256-021-00200-8
|View full text |Cite
|
Sign up to set email alerts
|

The comparison of epidemiological characteristics between confirmed and clinically diagnosed cases with COVID-19 during the early epidemic in Wuhan, China

Abstract: Background To put COVID-19 patients into hospital timely, the clinical diagnosis had been implemented in Wuhan in the early epidemic. Here we compared the epidemiological characteristics of laboratory-confirmed and clinically diagnosed cases with COVID-19 in Wuhan. Methods Demographics, case severity and outcomes of 29,886 confirmed cases and 21,960 clinically diagnosed cases reported between December 2019 and February 24, 2020, were compared. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…We identified 9937 potentially relevant records from the literature databases and registers, and 1575 records from the additional searches. After screening the titles, abstracts and full texts, 56 studies (22 cohort studies, 9 case-control studies, and 25 case series) with a total of 79,104 patients were included [ [10] , [11] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 9937 potentially relevant records from the literature databases and registers, and 1575 records from the additional searches. After screening the titles, abstracts and full texts, 56 studies (22 cohort studies, 9 case-control studies, and 25 case series) with a total of 79,104 patients were included [ [10] , [11] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 26 studies assessed risk factors for death [ 11 , 23 , 24 , 26 , 27 , 29 , 33 , 34 , [37] , [38] , [39] , [40] , [46] , [47] , [48] , 50 , 57 , 58 , 60 , 63 , 68 , 70 , [72] , [73] , [74] , [75] ]. We found low quality evidence that acute kidney injury (AKI, OR =3.15, 95% CI 1.25 to 7.90, two studies) was associated with an elevated risk of death.…”
Section: Resultsmentioning
confidence: 99%
“…This result is in agreement to the findings of Mahmoud et al [10] who estimated the fatality ratio to be 1.40 in Libya in a particular period of time. Shi et al [11] in China reported the risk factors for death were older age, male, severe or critical cases. In Ecuador, Ortiz-Prado et al [12] found the presence of comorbidities, being male and older than 65 years were important determinants of mortality.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 is a highly contagious respiratory disease with varying symptoms. According to the eighth edition of the COVID-19 Prevention and Control Plan, COVID-19 cases can be divided into mild, moderate, severe, and critical types (13). However, the symptoms at onset are relatively mild, and a significant proportion of patients do not display symptoms prior to the development of respiratory failure.…”
Section: Construction Of the Makeshift Hospitals And Response To Covi...mentioning
confidence: 99%